Adherence, persistence, and treatment discontinuation with sitagliptin compared with sulfonylureas as add‐ons to metformin: A retrospective cohort database study1: 在二甲双胍治疗的基础上比较加用西格列汀治疗与加用磺脲类药物治疗的依从性、持久性以及治疗中止:一项回顾性队列数据库研究. (7th October 2016) - Bloomgarden, Zachary T.; Tunceli, Kaan; Liu, Jinan; Brodovicz, Kimberly G.; Mavros, Panagiotis; Engel, Samuel S.; Radican, Larry; Chen, Yong; Rajpathak, Swapnil; Qiu, Ying; Brudi, Philippe; Fonseca, Vivian
Abstract: Background: Data are limited regarding adherence to dipeptidyl peptidase‐4 inhibitors. Methods: The present retrospective cohort study of a claims database involved adults with type 2 diabetes mellitus, continuous enrollment for 12 months before the first prescription of add‐on sitagliptin (SITA) or a sulfonylurea (SU) to metformin (MET) monotherapy (index date), and ≥45 days of MET coverage ≤90 days before the index date. The SITA and SU users were matched on duration of follow‐up and propensity score (PS). Logistic regression analysis incorporated age, gender, comorbidities, and concomitant medications as independent variables. Results: Approximately 99 % of SITA patients were PS matched, resulting in 14 807 well‐balanced PS‐matched SITA/SU pairs. Mean proportion of days covered (PDC) was significantly higher for SITA (vs SU) + MET after 1 year ( P  < 0.001). Adherence (PDC ≥80 %) to SITA (vs SU) + MET was 59.1 % (vs 55.9 %; P  < 0.001) at 1 year and 52.6 % (vs 49.9 %; P  = 0.007) at 2 years. Using logistic regression models including out‐of‐pocket expense (OPE) as a covariate, we found improved mean PDC and adherence for SITA (vs SU) + MET. Numbers of patients who continued to use SITA (vs SU) + MET were significantly higher after Years 1, 2, and 3 (all P  < 0.05). Conclusions: Users of SITA + MET had significantly higher mean PDC, adherence, and persistence than those on SU + MET. These trends were robust to model alterations and were more marked when accommodating OPEs. Abstract : (a) Proportion of days covered (PDC) and (b) proportion of study participants with PDC ≥80 % over time in Model 1 (unadjusted) comparing the sitagliptin + metformin (SITA + MET) group with the sulfonylurea (SU) + MET group. Highlights Treatment adherence and persistence for sitagliptin + metformin monotherapy were significantly higher than for sulfonylureas + metformin. The findings add to a growing body of evidence of the positive adherence profile for dipeptidyl peptidase‐4 inhibitors, which is not moderated by out‐of‐pocket expenses.